Organic metal complex and its synthesis method, organic copper complex synthesis method, film, organic electronics device, and organic electroluminescence element
Synthesis of macrocyclic metal organic composites through template reactions has solved the synthesis problems in the prior art and the problem of low equipment efficiency, and achieved efficient synthesis and excellent performance macrocyclic metal organic composites, which are suitable for organic electroluminescent equipment.
Patent Information
- Application Number
- JP2021140248
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-30
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-08-30
AI Technical Summary
It is difficult to effectively synthesize macrocyclic metal organic composites with excellent optical and electronic functions in the prior art, and it is used in the problems of high driving voltage and low external extraction efficiency in organic electroluminescent equipment.
The macrocyclic metal organic composite was synthesized by template reaction method, and the macrocyclic ligand was formed in the presence of metal atoms through a cyclization coupling reaction, and then the central metal atom was replaced to obtain the composite of other metal species.
It realizes efficient synthesis of macrocyclic metal organic composites with excellent optical and electronic functions, reduces the driving voltage and improves the external extraction efficiency, and is suitable for organic electroluminescent equipment.
Smart Images

Figure 0007655153000017 
Figure 0007655153000018 
Figure 0007655153000019
Abstract
Description
[Technical field]
[0001] The present invention relates to an organometallic complex and a method for synthesizing the same, A method for synthesizing organocopper complexes; More specifically, the present invention relates to an organometallic complex having excellent optical or electronic functions and a method for synthesizing the same, A method for synthesizing an organocopper complex; The present invention relates to providing a film and an organic electronic device containing the organometallic complex, in particular an organic electroluminescence element having a reduced driving voltage and improved light extraction efficiency. [Background technology]
[0002] Organic compounds with a ring structure consisting of approximately 10 or more atoms, such as porphyrins, macrolides, and crown ethers, are called macrocyclic compounds, and some of them can coordinate with metal atoms or ions at the center of the ring structure to form complexes.
[0003] Many of the organometallic complexes with such macrocyclic compounds as ligands have excellent optical or electronic functions and are used in various fields. For example, phthalocyanine has a planar structure with few steric hindrances, so that the π-electron conjugated system spreads throughout the molecule, and its copper complex has excellent color, clarity, and durability, so it is widely used in blue organic pigments, CD-Rs as recording media, organic electroluminescence elements, organic transistors, etc.
[0004] Such macrocyclic compounds have various functions due to their unique structures, and are expected to be used in a wide range of fields. However, there are only a limited number of simple and efficient methods for their production. For this reason, research and development has been conducted on simple and efficient methods for the production of macrocyclic compounds and organometallic complexes that have macrocyclic compounds as ligands.
[0005] Non-Patent Document 1 describes a method for synthesizing a cyclic compound in which six pyridines are bonded by single bonds. However, this synthesis method does not describe a method for selectively bonding both ends of the six bonded pyridines, and the yield of the cyclic compound was extremely low.
[0006] Non-Patent Documents 2 and 3 also do not disclose a method for selectively synthesizing a cyclic compound, and the yield of the cyclic compound was extremely low. In addition, the technique described in Non-Patent Document 2 can be used only when the central metal atom or ion is sodium, and there is room for further study on techniques using other metal species. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Newkome, GRet al. J. Am. Chem. Soc. 1983, 105, 5956. [Non-Patent Document 2] Toner,JLTetrahedron Lett.1983.24.2707. [Non-Patent Document 3] Bell,TWet al.J.Am.Chem.Soc.1986,108,8109 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made in consideration of the above problems and circumstances, and the problem to be solved by the present invention is to provide an organometallic complex having excellent optical or electronic functions, a method for synthesizing the same, A method for synthesizing an organocopper complex; The object of the present invention is to provide a film and an organic electronics device, particularly an organic electroluminescence element, which contains the organometallic complex and has a reduced driving voltage and improved light extraction efficiency. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have investigated the causes of the above problems and have found that an organometallic complex having a structure represented by the following general formula (1) has excellent optical or electrical functions, thereby completing the present invention. That is, the above-mentioned problems of the present invention are solved by the following means.
[0010] 1. Below Structural formulas: MO-7, MO-8, MO-9, MO-10, MO-11, MO-16, MO-17, MO-18, MO-20, MO-23 and MO-24 It has a structure represented by 1. An organometallic complex comprising:
[0011] [ka] [ka] [ka]
[0019] 2. Having a structure represented by the following general formula (3): A method for synthesizing an organometallic complex, comprising the steps of: The method includes a step of cyclizing the ligand by a coupling reaction in the presence of a metal atom or ion. death, The metal is Ni or Pd. 1. A method for synthesizing an organometallic complex comprising the steps of: [ka] (In the formula, R 1 ~R 3 Each independently represents a hydrogen atom or a substituent. M represents a metal atom or ion other than sodium. n represents a natural number of 4 to 8, and n R 1 ~R 3 are the same.) 3. After the step of cyclizing the ligand, a step of replacing the central metal atom or ion of the cyclized ligand by a reaction in the presence of a metal salt different from the metal used in the step of cyclizing the ligand. 3. The method for synthesizing the organometallic complex according to claim 2, 4. Use the method for synthesizing the organometallic complex described in item 3. 1. A method for synthesizing an organocopper complex comprising the steps of:
[0020] 5. No. 1 In the section The organometallic complexes described herein are A film characterized by:
[0021] 6. No. 1 In the section The present invention has an organic functional layer containing the organometallic complex described above. An organic electronics device comprising:
[0022] 7. No. 1 In the section The present invention has an organic functional layer containing the organometallic complex described above. An organic electroluminescence element comprising: Effect of the Invention
[0023] According to the above-mentioned means of the present invention, there are provided an organometallic complex having excellent optical or electronic functions, and a method for synthesizing the same; A method for synthesizing an organocopper complex; It is possible to provide a film and an organic electronic device containing the organometallic complex, in particular an organic electroluminescence element with a reduced driving voltage and improved light extraction efficiency.
[0024] Although the mechanism by which the effects of the present invention are manifested or the mechanism by which the effects of the present invention are acted upon has not been clearly understood, it is speculated as follows.
[0025] Many macrocyclic compounds have excellent functions and are expected to be used in a wide range of fields, but there are only a limited number of simple and efficient methods for their production (synthesis). For this reason, research and development has been conducted on simple and efficient methods for the production of macrocyclic compounds.
[0026] In general, in the cyclization reaction for synthesizing macrocyclic compounds, the probability of the desired reaction points meeting each other is low, so it is easy to produce compounds in which the reactants are bonded in a chain shape, and it is difficult to produce cyclic compounds. The highly dilution method described below is used to improve the yield of cyclic compounds, but it requires a large amount of solvent, which is technically and costly.
[0027] As a result of extensive investigations, the present inventors have found that by using the template reaction described below, cyclic compounds can be synthesized in high yields while minimizing technical and cost burdens. In addition, by using this template reaction, an organometallic complex having a macrocyclic compound as a ligand is formed, and this organometallic complex has been found to have excellent optical and electronic functions. Furthermore, the metal species of the organometallic complex formed here is the specific metal species used in the template reaction, but it has been found that by replacing the central metal species after synthesizing the macrocyclic compound, organometallic complexes using other metal species can be synthesized. [Brief description of the drawings]
[0028] [Figure 1] Schematic diagram showing an example of the configuration of an organic EL element [Diagram 2] Schematic diagram showing the mechanism of charge flow and light emission in an organic EL element [Diagram 3] A schematic diagram showing an example of a solar cell made of a bulk heterojunction type organic photoelectric conversion element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The organometallic complex of the present invention is characterized by having a structure represented by the above general formula (1). This feature is a technical feature common to or corresponding to the following embodiments.
[0030] As an embodiment of the present invention, from the viewpoint of exerting the effects of the present invention, it is preferable that the organometallic complex has a structure represented by the above general formula (2), and more preferably has a structure represented by the above general formula (3).
[0031] The method for synthesizing an organometallic complex of the present invention is characterized by having a step of cyclizing a ligand by a coupling reaction in the coexistence of a metal atom or ion.
[0032] The organometallic complex of the present invention is preferably contained in a film.
[0033] Furthermore, the organometallic complex of the present invention is suitably contained in an organic functional layer constituting an organic electronics device or an organic electroluminescence element.
[0034] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values before and after the symbol "to" are included as the lower limit and upper limit.
[0035] <<Summary of the organometallic complex of the present invention>> The organometallic complex of the present invention is characterized by having a structure represented by the following general formula (1).
[0036] [ka]
[0037] (In the formula, M represents a metal atom or ion other than sodium. Each Ar1 independently represents a divalent aromatic hydrocarbon group or aromatic heterocyclic group, which may have a substituent or may be a condensed ring. m represents a natural number of 0 to 6. When m represents a natural number of 2 to 6, m Ar1s may all be the same or all different. Each Ar2 independently represents a divalent aromatic heterocyclic group having at least one nitrogen atom bonded to a metal atom or ion M, which may have a substituent or may be a condensed ring. n represents a natural number of 1 to 6. When n represents a natural number of 2 to 6, n Ar2s may all be the same or all different. In addition, m and n satisfy 4≦m+n≦12. The bonding order of m Ar1s and n Ar2s is not particularly limited.)
[0038] In the present invention, the term "complex" refers to an atomic group formed by directional three-dimensional bonding of several other atoms, ions, molecules, or atomic groups (these are called "ligands") around a single atom or ion at the center. The bond is represented by the dotted line connecting the metal atom or ion M and Ar2 in the above general formula (1).
[0039] Among complexes, those in which the central atom or ion is a metal atom or ion are called "metal complexes", and those in which the ligand is an organic compound are called "organometallic complexes".
[0040] The organometallic complex of the present invention is formed by binding a macrocyclic compound composed of Ar1 and Ar2, or Ar2 alone, to a metal atom or ion M. Specifically, as shown by the dotted line in the above general formula (1), one nitrogen atom in Ar2 is bound to a metal atom or ion M. Although the mechanism of this binding cannot be determined, it is believed to be bound by a coordinate bond. Note that the atom in Ar1 and the metal atom or ion M may or may not be bound.
[0041] The term "coordinate bond" refers to a chemical bond in which bonding electrons are provided to a molecular orbital from only one of the two atoms forming the bond. In the present invention, it is considered that the unshared electron pair of one nitrogen atom in Ar2 is provided to form a coordinate bond with a metal atom or ion M.
[0042] In the organometallic complex of the present invention, the macrocyclic compound as the ligand has a cyclic structure, and one nitrogen atom in Ar2 that forms a coordinate bond with a metal atom or ion M is located inside the cyclic structure. By having a nitrogen atom located inside the cyclic structure, it becomes easier for a metal atom or ion to be coordinated to the center of the cyclic structure.
[0043] As shown by the curve of the above general formula (1), the macrocyclic compound according to the present invention has a structure in which m Ar1 and n Ar2 are mutually bonded by one single bond, and among them, Ar2 contributes to a coordinate bond with a metal atom or ion M. Ar2 may contain two or more nitrogen atoms, but only one of them contributes to a coordinate bond with a metal atom or ion M. Therefore, the number of coordinate bonds between the macrocyclic compound and a metal atom or ion M is n, and n can be a natural number from 1 to 6, so that the number of coordinate bonds in the organometallic complex of the present invention is within the range of 1 to 6. By changing the number of coordinate bonds, the properties of the organometallic complex of the present invention can be changed.
[0044] As an example, consider the case where the metal atom or ion M is Ni. The coordination number of the metal atom or ion is specific to each metal, and Ni can have a coordination number of 4 or 6. When the coordination number is 4, all four coordination bonds are on a plane, so it is preferable from the viewpoint of stability that the compound has four coordination bonds with the macrocyclic compound. When the coordination number is 6, it is preferable from the viewpoint of stability that the compound has four coordination bonds with the macrocyclic compound and two coordination bonds with other ligands.
[0045] The coordination number of the metal atom or ion M is not limited, and may have five coordination bonds with a macrocyclic compound and further have coordination bonds with two chloride ions, as in MO-9 shown in the production method of the organometallic complex of the present invention described later.
[0046] The number of coordinate bonds in the organometallic complex of the present invention can be selected depending on the types of Ar1 and Ar2 and the type of the central metal atom or ion.
[0047] m and n satisfy the relationship 4≦m+n≦12. If the value of m+n is 3 or less, a cyclic structure cannot be formed, or even if a cyclic structure can be formed, a metal atom or ion cannot enter the hole at the center of the ring, and an organometallic complex cannot be formed. If the value of m+n is 13 or more, the hole becomes too large, and the distance between the metal atom or ion M and the nitrogen atom becomes large, making it difficult to form a coordinate bond.
[0048] m and n are preferably 4≦m+n≦8, and more preferably 5≦m+n≦6. When the value of m+n is within the above range, the macrocyclic compound has a planar structure with little steric hindrance, so that the π-electron conjugated system spreads easily throughout the molecule. In addition, the size of the vacancy is neither too small nor too large, so that the metal atom or ion M and the nitrogen atom can easily form a coordinate bond.
[0049] Each Ar1 independently represents a divalent aromatic hydrocarbon group or aromatic heterocyclic group, and may have a substituent or may be a condensed ring. Ar1 may or may not be bonded to a metal atom or ion M. Furthermore, m represents a natural number of 0 to 6. When m represents a natural number of 2 to 6, m Ar1 may be the same or different.
[0050] The term "divalent aromatic hydrocarbon group (also referred to as "arylene group")" refers to a divalent group obtained by removing two hydrogen atoms directly bonded to carbon atoms constituting a ring from an aromatic hydrocarbon, and a divalent group to which a plurality of such divalent groups (e.g., 2 to 5) are bonded. The number of carbon atoms in the divalent aromatic hydrocarbon group is usually 6 to 60, preferably 6 to 30, and more preferably 6 to 18.
[0051] Examples of the divalent aromatic hydrocarbon group include a phenylene group, a naphthalene-diyl group, an anthracene-diyl group, a phenanthrene-diyl group, a dihydrophenanthrene-diyl group, a naphthacene-diyl group, a fluorene-diyl group, a pyrene-diyl group, a perylene-diyl group, and a chrysene-diyl group.
[0052] In addition, the term "divalent aromatic heterocyclic group" refers to a divalent group obtained by removing, from an aromatic heterocyclic compound, two hydrogen atoms from among the hydrogen atoms directly bonded to carbon atoms or heteroatoms constituting the ring, and a divalent group to which a plurality (e.g., 2 to 4) selected from the group consisting of such divalent groups is bonded.
[0053] Examples of divalent aromatic heterocyclic groups (also referred to as "heteroarylene groups") include a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a thienylene (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimido-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group, a thienoxazole-diyl group, a dibenzofuran-diyl group, a dibenzothiophene-diyl group, and a carbazole-diyl group.
[0054] These aromatic groups (aromatic hydrocarbon groups and aromatic heterocyclic groups) may have a substituent at any position. Examples of the substituent include aromatic groups such as a phenyl group, a pyridyl group, a pyrrole group, a thienyl group, a furyl group, an imidazolyl group, a pyrimidyl group, a pyrazyl group, a pyridazyl group, and a triazinyl group, and condensed aromatic groups obtained by further condensing these groups (e.g., a naphthyl group, a quinolyl group, an imidazolyl group, an indoloimidazolyl group, an imidazoimidazolyl group, a dibenzothienyl group, a dibenzofuryl group, an azadibenzofuryl group, a benzimidazolyl group, a quinazolyl group, a benzopi group, and the like). Examples of substituents include substituents such as aryl groups, aryl groups, aryl groups, arylthio groups, amino groups, carbonyl groups, acyl groups, ester groups, ureido groups, and urethane groups, and halogen atoms such as fluorine atoms and chlorine atoms. Among these, aromatic groups (including condensates), aliphatic groups, cyano groups, alkoxy groups, and fluorine atoms are preferred.
[0055] Each Ar2 independently represents a divalent aromatic heterocyclic group having at least one nitrogen atom bonded to a metal atom or ion M, and may have a substituent or may be a condensed ring. n represents a natural number of 1 to 6. When n represents a natural number of 2 to 6, the n Ar2 may be the same or different.
[0056] Accordingly, Ar2 is a divalent aromatic heterocyclic group having a nitrogen atom, and examples thereof include a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimido-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienoxazole-diyl group, and a carbazole-diyl group.
[0057] The metal atom or ion M is not particularly limited as long as it is other than sodium, and examples thereof include Li, K, Mg, Ca, Sr, Ti, Cr, Mn, Fe, Co, Ni, Cu, Pd, Ag, Rh, Pt, Au, La, Ce, Er, and ions thereof, among which Pd, Pt, Ag, Ni, Au, Rh, Ir, Co, Cu, and ions thereof are particularly preferred.
[0058] There is no particular restriction on the metal atom or ion M, but the metal that can be coordinated is selected depending on the size of the cavity of the macrocyclic compound. Furthermore, the properties of the organometallic complex formed vary greatly depending on the metal that is coordinated.
[0059] Examples of the organometallic complex of the present invention are shown below. However, the present invention is not limited to these. In the following chemical structural formula, the bond between one nitrogen atom in Ar2 and a metal atom or ion M is shown by a dotted line, and the bond between an atom in Ar1 and a metal atom or ion is shown by a solid line. Also, the * mark in R of MO-20 indicates the bond site with the Eu atom.
[0060] [ka]
[0061] [ka]
[0062] [ka]
[0063] <Method for producing organometallic complex of the present invention> The method for producing (synthesizing) an organometallic complex of the present invention is characterized by having a step of cyclizing a ligand by a coupling reaction in the co-presence of a metal atom or ion.
[0064] The method for producing an organometallic complex of the present invention further comprises 1) a step of cyclizing a ligand by a coupling reaction in the presence of a metal atom or ion, and, if necessary, 2) a step of replacing the central metal atom or ion.
[0065] Usually, when synthesizing macrocyclic compounds, the probability of the desired reaction points meeting each other is low, so compounds in which the reactants are linked in a chain are likely to be produced, and it is difficult to produce cyclic compounds. Therefore, a method (high dilution method) is used to increase the relative probability of the desired reaction points meeting each other by using a much larger amount of solvent than usual, thereby improving the yield of cyclic compounds. However, since a large amount of solvent is required, this method imposes a large technical and cost burden.
[0066] The organometallic complex of the present invention can synthesize a cyclic compound in high yield by inducing a coupling reaction under template reaction without using such a high dilution method.
[0067] The term "template reaction" refers to a method for synthesizing an organic compound in which the reactant forms a coordinate bond with a metal atom or ion by coexistence of the metal atom or ion, and the synthesis proceeds in a positional state suitable for cyclization. In the present invention, it is considered that the unshared electron pair of one nitrogen atom in Ar2 in the above general formula (1) is provided to form a coordinate bond with the metal atom or ion M.
[0068] However, since the template reaction occurs only in the presence of certain metal atoms or ions such as Ni or Pd, organometallic complexes using other metal atoms or ions can be synthesized by cyclizing the ligand through a coupling reaction in the presence of metal atoms or ions such as Ni or Pd, and then replacing the central metal atom or ion.
[0069] An example of the method for producing the organometallic complex of the present invention will now be described.
[0070] [ka]
[0071] (A step of cyclizing the ligand by a coupling reaction in the presence of a metal atom or ion) 2,2'-bipyridyl (23.4 g, 150.0 mmol), 1,5-cyclooctadiene (18.4 mL, 150.0 mmol), bis(1,5-cyclooctadiene)nickel(0) (41.3 g, 150.0 mmol) were added with DMF (62.5 mL) and toluene (62.5 mL) and stirred at 80 °C for 30 min. A solution of compound 2 (3.78 g, 15.0 mmol) in toluene (250 mL) was added dropwise to the mixture over 1 h and stirring was continued at 80 °C for another 16 h. The reaction mixture was cooled to room temperature, 2 M hydrochloric acid (300 mL) was added, and the mixture was stirred vigorously overnight under air. It was extracted with CHCl (400 mL × 3), and the organic layer was washed with saturated brine (200 mL), dried over NaSO, and concentrated in vacuum. The crude product was passed through a silica gel short pass (eluent: CHCl3:MeOH=20:1) and further purified by GPC (YMC T30000, T4000, T2000 columns, solvent: CHCl3) to obtain compound MO-9 as a yellow solid in a yield of 57% (1.77 g, 1.71 mmol). Mass spectrometry (MALDI-TOF MS) confirmed that the product was compound MO-9.
[0072] (Process of replacing the central metal atom or ion) The copper complex MO-11 was produced by synthesis in exactly the same manner as in Example 1, except that 10 equivalents of CuCl (14.9 g, 150 mmol) was added to a DMF / toluene solution of 2,2'-bipyridyl, 1,5-cyclooctadiene, and bis(1,5-cyclooctadiene)nickel(0). Mass spectrometry revealed that the product was compound MO-11.
[0073] <Film of the present invention> The organometallic complex of the present invention has excellent optical or electronic functions, and can be used in various applications by forming it into a film, such as luminous plastics, luminescent color control films for displays, temperature-sensitive sheets, etc. The organometallic complex of the present invention has high stability because it can utilize thermodynamic stability by using a cyclic ligand, and is particularly useful as a color filter for displays.
[0074] The thickness of the film of the present invention is not particularly limited, but is preferably within the range of 10 to 1500 μm, and more preferably within the range of 20 to 1000 μm.
[0075] The film of the present invention may be formed as a single layer film on a substrate having a release layer and then peeled off, or may be formed on a substrate to form a laminate film having various functional layers.
[0076] The film of the present invention can be produced by blending an organometallic complex with a plastic material. The blending amount of the organometallic complex is preferably within the range of 1 to 50% by mass with respect to the total mass of the plastic material. The plastic material is not particularly limited, and examples thereof include polyethylene resin, polypropylene resin, polyvinyl chloride resin, urea resin, fluororesin, polyester resin, polyamide resin, polyacetal resin, polycarbonate resin, polyarylate resin, polysulfone resin, polyphenylene sulfide resin, polyethersulfone resin, polyarylsulfone resin, polytetrafluoroethylene resin, phenol resin, unsaturated polyester resin, epoxy resin, polyimide resin, polyamideimide resin, etc.
[0077] The method for producing the film is not particularly limited, and the film can be produced by a conventionally known method. The method for forming an organic functional layer in the method for producing an organic electroluminescence element described later may also be used.
[0078] A film can also be produced by polymerizing the macrocyclic compound, which is a ligand. A method for polymerizing a macrocyclic compound can be used that is described in a known synthesis method (Non-Patent Document: Polymer Chemistry, Synthesis, by Nakajo Yoshiki et al., Maruzen Publishing, published in June 2010). For example, there is a method in which a polymerizable substituent such as a vinyl group or an epoxy group is introduced into the molecule in advance and a polymer is obtained by chain polymerization, or a method in which a halogen substituent (also called a "halogeno group") is introduced into the molecule and condensation polymerization is performed by dehalogenating it.
[0079] <Organic electronic device of the present invention> The organic electronics device of the present invention is characterized by having an organic functional layer containing the organometallic complex of the present invention. The organometallic complex of the present invention has excellent optical or electronic functions, and its use as a material constituting the organic functional layer can improve the performance of the organic electronics device.
[0080] Examples of organic electronic devices include organic electroluminescence elements, organic solar cells, organic transistors, etc. Hereinafter, the organic electroluminescence elements and organic solar cells will be described.
[0081] [Organic electroluminescence element] The organic electronics device of the present invention is characterized by having an organic functional layer containing the organometallic complex of the present invention. The organometallic complex of the present invention has excellent optical and electronic functions and can be suitably used as a material for an organic electroluminescence element (hereinafter also referred to as an "organic EL element").
[0082] Representative device configurations for an organic EL device produced using the organometallic complex of the present invention include the following configurations. Among them, the configuration (vii) is preferably used, but is not limited thereto. (i) Anode / Emitting layer / Cathode (ii) anode / light-emitting layer / electron transport layer / cathode (iii) anode / hole transport layer / light emitting layer / cathode (iv) anode / hole transport layer / light emitting layer / electron transport layer / cathode (v) anode / hole transport layer / light emitting layer / electron transport layer / electron injection layer / cathode (vi) Anode / hole injection layer / hole transport layer / light emitting layer / electron transport layer / cathode (vii) anode / hole injection layer / hole transport layer / (electron blocking layer / )light-emitting layer / (hole blocking layer / )electron transport layer / electron injection layer / cathode
[0083] In the organic EL device of the present invention, the light-emitting layer is composed of a single layer or multiple layers, and when the light-emitting layer is multiple, a non-light-emitting intermediate layer may be provided between each of the light-emitting layers. If necessary, a hole-blocking layer (also called a "hole-blocking layer") or an electron-injecting layer (also called a "cathode buffer layer") may be provided between the light-emitting layer and the cathode, and an electron-blocking layer (also called an "electron-blocking layer") or a hole-injecting layer (also called an anode buffer layer) may be provided between the light-emitting layer and the anode.
[0084] The electron transport layer according to the present invention is a layer having a function of transporting electrons, and in a broad sense, the electron transport layer also includes an electron injection layer and a hole blocking layer. Also, the electron transport layer may be composed of a plurality of layers.
[0085] The hole transport layer according to the present invention is a layer having a function of transporting holes, and in a broad sense, the hole transport layer also includes a hole injection layer and an electron blocking layer. It may also be composed of multiple layers. In the above representative element configuration, the layers excluding the anode and cathode are called "organic functional layers."
[0086] The organic EL device of the present invention has an organic functional layer containing the above-mentioned organometallic complex. That is, in the structures (i) to (vii), the above-mentioned organometallic complex may be contained in any layer other than the anode and the cathode.
[0087] Fig. 1 is a schematic diagram showing an example of the configuration of an organic EL element, which corresponds to the configuration shown in (vi). In Fig. 1, a hole injection layer 4, a hole transport layer 5, a light emitting layer 6, and an electron transport layer 7 are organic functional layers F.
[0088] FIG. 2 is a schematic diagram showing the mechanism of charge flow and light emission in an organic EL element. When a voltage is applied to the organic EL element 1, electrons (e - ) is transferred from the anode 3 to the hole injection layer 4 as a hole (h + ) is injected.
[0089] The electrons and holes are then transported to the adjacent organic layers on the opposite side of the electrode, the electron transport layer 7 and the hole transport layer 5, respectively.
[0090] Finally, the electrons and holes that meet in the light-emitting layer 6 recombine R to generate excitons, and when these return from the excited state to the ground state, light (fluorescence / phosphorescence) L is emitted. In FIG. 2, the organic functional layer F is made up of layers from the hole injection layer 4 to the electron injection layer 8.
[0091] The organic EL element of the present invention may be an element having a so-called tandem structure in which a plurality of light-emitting units, each of which has at least one light-emitting layer, are stacked. In the tandem structure, all layers except the anode and cathode are referred to as the "organic functional layer".
[0092] A typical element configuration of the tandem structure is, for example, as follows. Anode / First light-emitting unit / Second light-emitting unit / Third light-emitting unit / Cathode Anode / First light-emitting unit / Intermediate layer / Second light-emitting unit / Intermediate layer / Third light-emitting unit / Cathode
[0093] Here, the first light-emitting unit, the second light-emitting unit, and the third light-emitting unit may all be the same or different. Alternatively, two light-emitting units may be the same and the remaining one may be different. Furthermore, the third light-emitting unit may be omitted, while another light-emitting unit or intermediate layer may be provided between the third light-emitting unit and the electrode.
[0094] The plurality of light-emitting units may be stacked directly or via an intermediate layer. The intermediate layer is generally also called an intermediate electrode, an intermediate conductive layer, a charge generating layer, an electron extracting layer, a connecting layer, or an intermediate insulating layer. Any known material and configuration may be used as long as the intermediate layer has the function of supplying electrons to an adjacent layer on the anode side and holes to an adjacent layer on the cathode side.
[0095] The material used for the intermediate layer is not particularly limited, and examples thereof include ITO (indium tin oxide), IZO (indium zinc oxide), ZnO2, TiN, ZrN, HfN, TiO x , V.O. x, CuI, InN, GaN, CuAlO2, CuGaO2, SrCu2O2, LaB6, RuO2, Al and other conductive inorganic compound layers, bilayer films such as Au / Bi2O3, multilayer films such as SnO2 / Ag / SnO2, ZnO / Ag / ZnO, Bi2O3 / Au / Bi2O3, TiO2 / TiN / TiO2, TiO2 / ZrN / TiO2, and C 60 conductive organic layer such as oligothiophene; conductive organic compound layer such as metal phthalocyanines, metal-free phthalocyanines, metal porphyrins, metal-free porphyrins, etc.
[0096] A preferred configuration within the light-emitting unit is not particularly limited, and examples thereof include those in which the anode and cathode are removed from the configurations (i) to (vii) given as the representative device configurations above.
[0097] Specific examples of the tandem type organic EL element are not particularly limited, and include, for example, those described in U.S. Pat. No. 6,337,492, U.S. Pat. No. 7,420,203, U.S. Pat. No. 7,473,923, U.S. Pat. No. 6,872,472, U.S. Pat. No. 6,107,734, U.S. Pat. No. 6,337,492, International Publication No. 2005 / 009087, JP-A No. 2006-228712, JP-A No. 2006-24791, JP-A No. 2006-49393, JP-A No. 2006-49394, and JP-A No. 2006-49396. JP-A-2011-96679, JP-A-2005-340187, Japanese Patent No. 4711424, Japanese Patent No. 3496681, Japanese Patent No. 3884564, Japanese Patent No. 4213169, JP-A-2010-192719, JP-A-2009-076929, JP-A-2008-078414, JP-A-2007-059848, JP-A-2003-272860, JP-A-2003-045676, WO 2005 / 094130 and the like.
[0098] <1. Components of an organic electroluminescence element> Each layer constituting the organic EL device of the present invention will be described below.
[0099] (Light Emitting Layer) The term "light-emitting layer" refers to a layer that provides a site where electrons and holes injected from an electrode or an adjacent layer recombine and emit light via excitons. The light-emitting portion may be within the light-emitting layer or at the interface between the light-emitting layer and an adjacent layer.
[0100] In addition, there may be a plurality of layers having the same emission spectrum or maximum emission wavelength. In this case, it is preferable to have a non-light-emitting intermediate layer between each of the light-emitting layers. The structure of the light-emitting layer according to the present invention is not particularly limited as long as it satisfies the requirements defined in the present invention.
[0101] The total thickness of the light-emitting layers is not particularly limited, but from the viewpoints of homogeneity of the layer to be formed, prevention of application of unnecessary high voltage during light emission, and improvement of stability of the emitted color against the driving current, it is preferably within the range of 2 nm to 5 μm, more preferably within the range of 2 to 500 nm, and even more preferably within the range of 5 to 200 nm. When a non-light-emitting intermediate layer is present between the light-emitting layers, the thickness of the intermediate layer is also included in the total thickness of the light-emitting layers.
[0102] The light-emitting layer preferably contains a light-emitting dopant (hereinafter also referred to as a "light-emitting dopant compound", "dopant compound", or simply "dopant") and a host compound (hereinafter also referred to as a "matrix material", "light-emitting host compound", or simply "host"), and it is preferable for light to be emitted from the light-emitting material.
[0103] (1) Light-emitting dopants As the light-emitting dopant, a fluorescent dopant (hereinafter also referred to as a "fluorescent dopant" or a "fluorescent compound") and a phosphorescent dopant (hereinafter also referred to as a "phosphorescent dopant" or a "phosphorescent compound") are preferably used. In the present invention, it is particularly preferable to use a phosphorescent dopant or a thermally activated delayed fluorescent compound (TADF) among the fluorescent dopants.
[0104] The concentration of the light-emitting dopant in the light-emitting layer can be determined arbitrarily based on the specific dopant used and the requirements of the device, and may be uniform or have an arbitrary concentration distribution across the thickness of the light-emitting layer.
[0105] In addition, a plurality of light-emitting dopants may be used in combination, or dopants having different structures may be used in combination, or a fluorescent dopant and a phosphorescent dopant may be used in combination, thereby making it possible to obtain any emission color.
[0106] The emitted color of an organic EL element is determined by the color measured using a spectroradiometer CS-1000 (manufactured by Konica Minolta, Inc.) and applied to the CIE chromaticity coordinates, as shown in Figure 4.16 on page 108 of the "New Color Science Handbook" (edited by the Color Science Association of Japan, University of Tokyo Press, 1985).
[0107] In the present invention, it is also preferable that the light-emitting layer or layers contain a plurality of light-emitting dopants that emit light of different colors and emit white light. The combination of light-emitting dopants that exhibit white color is not particularly limited, and examples thereof include combinations of blue and orange, and blue, green and red. The white color in the present invention is not particularly limited and may be a white color leaning toward orange or a white color leaning toward blue. However, when the 2-degree viewing angle front luminance is measured by the above-mentioned method, the white color is 1000 cd / m 2 It is preferable that the chromaticity in the CIE 1931 color system at is within the range of x=0.39±0.09, y=0.38±0.08.
[0108] (1.1) Phosphorescent dopant The phosphorescent dopant according to the present invention (hereinafter, also referred to as "phosphorescent dopant") will be described. A phosphorescent dopant is a compound in which light emission from an excited triplet state is observed, and specifically, is defined as a compound that emits phosphorescence at room temperature (25° C.) and has a phosphorescence quantum yield of 0.01 or more at 25° C., with a phosphorescence quantum yield of 0.1 or more being preferred.
[0109] The phosphorescence quantum yield can be measured by the method described in Spectroscopy II, p. 398, of Experimental Chemistry Lectures 7, 4th Edition (1992 edition, Maruzen). The phosphorescence quantum yield in a solution can be measured using various solvents, and the phosphorescent dopant according to the present invention may be any solvent that achieves the phosphorescence quantum yield (0.01 or more).
[0110] There are two types of principle for the emission of phosphorescent dopants. One is an energy transfer type in which carrier recombination occurs on the host compound to which the carriers are transported, generating an excited state of the host compound, and this energy is transferred to the phosphorescent dopant to obtain emission from the phosphorescent dopant. The other is a carrier trap type in which the phosphorescent dopant acts as a carrier trap, carrier recombination occurs on the phosphorescent dopant, and emission from the phosphorescent dopant is obtained. In either case, the condition is that the energy of the excited state of the phosphorescent dopant is lower than the energy of the excited state of the host compound.
[0111] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the phosphorescent dopant. Among them, the organometallic complex in which the central metal atom or ion M is Ir or Pt is preferable.
[0112] In addition to the above metal complexes, known phosphorescent dopants used in the light-emitting layer of organic EL devices can be used. The above metal complexes and known phosphorescent dopants may be used in combination. Specific examples of known phosphorescent dopants include compounds described in the following documents.
[0113] Nature 395,151(1998), Appl. Phys. Lett. 78,1622(2001), Adv. Mater. 19,739(2007), Chem. Mater. 17,3532(2005), Adv. Mater. 17,1059(2005), WO 2009 / 100991, WO 2008 / 101842, WO 2003 / 040257, U.S. Patent Publication No. 2006 / 835469, U.S. Patent Publication No. 2006 / 0202194, U.S. Patent Publication No. 2007 / 0087321, U.S. Patent Publication No. 2005 / 0244673, Inorg.Chem.40,1704(2001), Chem.Mater.16,2480(2004), Adv.Mater.16,2003(2004), Angew.Chem.Int.Ed.2006,45,7800, Appl.Phys.Lett.86,153505(2005), Chem.Lett.34,592(2005), Chem.Commun.2906(2005), Inorg.Chem.42,1248(2003), International Publication No. 2009 / 050290, International Publication No. No. 002 / 015645, International Publication No. 2009 / 000673, U.S. Patent Publication No. 2002 / 0034656, U.S. Patent No. 7,332,232, U.S. Patent Publication No. 2009 / 0108737, U.S. Patent Publication No. 2009 / 0039776, U.S. Patent No. 6,921,915, U.S. Patent No. 6,687,266, U.S. Patent Publication No. 2007 / 0190359, U.S. Patent Publication No. 2006 / 0008670, U.S. Patent Publication No. 2009 / 0165846, U.S. Patent Publication No. 2008 / 0015355 , U.S. Patent No. 7,250,226, U.S. Patent No. 7,396,598, U.S. Patent Publication No. 2006 / 0263635, U.S. Patent Publication No. 2003 / 0138657, U.S. Patent Publication No. 2003 / 0152802, U.S. Patent No. 7,090,928, Angew.Chem.Int.Ed. 47,1 (2008), Chem.Mater. 18,5119 (2006), Inorg.Chem. 46,4308 (2007), Organometallics 23,3745 (2004), Appl.Phys.Lett.74,1361 (1999), International Publication No. 2002 / 002714, International Publication No. 2006 / 009024, International Publication No. 2006 / 056418, International Publication No. 2005 / 019373, International Publication No. 2005 / 123873, International Publication No. 2007 / 004380, International Publication No. 2006 / 082742, U.S. Patent Publication No. 2006 / 0251923, U.S. Patent Publication No. 2005 / 0260441, U.S. US Patent No. 7393599, US Patent No. 7534505, US Patent No. 7445855, US Patent Publication No. 2007 / 0190359, US Patent Publication No. 2008 / 0297033, US Patent No. 7338722, US Patent Publication No. 2002 / 0134984, US Patent No. 7279704, US Patent Publication No. 2006 / 098120, US Patent Publication No. 2006 WO 2005 / 076380, WO 2010 / 032663, WO 2008 / 140115, WO 2007 / 052431, WO 2011 / 134013, WO 2011 / 157339, WO 2010 / 086089, WO 2009 / 113646, WO 2012 / 020327, WO 2011 / 05140 4, International Publication No. 2011 / 004639, International Publication No. 2011 / 073149, U.S. Patent Publication No. 2012 / 228583, U.S. Patent Publication No. 2012 / 212126, JP 2012-069737 A, JP 2012-195554 A, JP 2009-114086 A, JP 2003-81988 A, JP 2002-302671 A, JP 2002-363552 A, and the like.
[0114] (1.2) Fluorescent dopants The fluorescent dopant according to the present invention (hereinafter, also referred to as "fluorescent dopant") will be described. The fluorescent dopant is a compound capable of emitting light from an excited singlet state, and is not particularly limited as long as light emission from the excited singlet state can be observed.
[0115] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the fluorescent dopant. Among them, the organometallic complex in which the central metal atom or ion M is Cu or Eu is preferable.
[0116] In addition to the above metal complexes, known fluorescent dopants used in the light-emitting layer of organic EL elements can be used. The above metal complexes and known fluorescent dopants can be used in combination. Specific examples of known fluorescent dopants include compounds described in the following documents.
[0117] Examples of the fluorescent dopant according to the present invention include anthracene derivatives, pyrene derivatives, chrysene derivatives, fluoranthene derivatives, perylene derivatives, fluorene derivatives, arylacetylene derivatives, styrylarylene derivatives, styrylamine derivatives, arylamine derivatives, boron complexes, coumarin derivatives, pyran derivatives, cyanine derivatives, croconium derivatives, squarium derivatives, oxobenzanthracene derivatives, fluorescein derivatives, rhodamine derivatives, pyrylium derivatives, perylene derivatives, polythiophene derivatives, and rare earth complex compounds.
[0118] In addition, a thermally activated delayed fluorescent compound may be used. Specific examples thereof include compounds described in International Publication No. 2011 / 156793, JP-A No. 2011-213643, JP-A No. 2010-93181, etc., but the present invention is not limited thereto.
[0119] (2) Host compound The host compound according to the present invention is a compound that mainly injects and transports charges in the light-emitting layer, and does not substantially emit light by itself in the organic EL device. The host compound is preferably a compound having a phosphorescence quantum yield of phosphorescence emission at room temperature (25° C.) of less than 0.1, and more preferably a compound having a phosphorescence quantum yield of less than 0.01.
[0120] The content of the host compound is preferably 20% by mass or more based on the total mass of the compounds contained in the light-emitting layer. The excited state energy of the host compound is preferably higher than the excited state energy of the light-emitting dopant contained in the same layer.
[0121] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the host compound. Among them, an organometallic complex in which the central metal atom or ion M is Ir is preferable.
[0122] In addition to the above metal complexes, known host compounds used in the light-emitting layer of an organic EL device can be used. The above metal complexes can also be used in combination with known host compounds.
[0123] The host compound may be a low molecular weight compound, a polymeric compound having a repeating unit, or a compound having a reactive group such as a vinyl group or an epoxy group. The host compound may be used alone or in combination of two or more kinds. By using two or more kinds of host compounds in combination, the charge transfer can be adjusted, and the efficiency of the organic EL element can be increased.
[0124] In addition, from the viewpoint of having hole transporting ability or electron transporting ability, preventing the emission wavelength from becoming longer, and further allowing the organic EL element to stably operate at high temperatures or against heat generation during element operation, it is preferable that the host compound has a high glass transition temperature (Tg). The Tg is preferably 90° C. or higher, more preferably 120° C. or higher. Here, the glass transition point (Tg) is a value determined by a method based on JIS-K-7121 using DSC (Differential Scanning Calorimetry).
[0125] Specific examples of known host compounds include compounds described in the following documents, but the present invention is not limited to these. JP 2001-257076 A, JP 2002-308855 A, JP 2001-313179 A, JP 2002-319491 A, JP 2001-357977 A, JP 2002-334786 A, JP 2002-8860 A, JP 2002-334787 A, JP 2002-15871 A, JP 2002-334788 A, JP 2002-43056 A, JP 2002-334789 A, JP 2002-75645 A, JP 2002-338579 A, JP 2002-1 JP-A-05445, JP-A-2002-343568, JP-A-2002-141173, JP-A-2002-352957, JP-A-2002-203683, JP-A-2002-363227, JP-A-2002-231453, JP-A-2003-3165, JP-A-2002-234888, JP-A-2003-27048, JP-A-2002-255934, JP-A-2002-260861, JP-A-2002-280183, JP-A-2002-299060, JP-A-2002-302516 JP 2002-305083 A, JP 2002-305084 A, JP 2002-308837 A, U.S. Patent Publication No. 2003 / 0175553, U.S. Patent Publication No. 2006 / 0280965, U.S. Patent Publication No. 2005 / 0112407, U.S. Patent Publication No. 2009 / 0017330, U.S. Patent Publication No. 2009 / 0030202, U.S. Patent Publication No. 2005 / 0238919, International Publication No. 2001 / 039234, International Publication No. 2009 / 021126, International Publication No. 2008 / 056746, WO 2004 / 093207, WO 2005 / 089025, WO 2007 / 063796, WO 2007 / 063754, WO 2004 / 107822, WO 2005 / 030900, WO 2006 / 114966, WO 2009 / 086028, WO 2009 / 003898, WO 2012 / 023947, JP 2008-074939 A, JP 2007-254297 A, EP 2034538 specification, etc.
[0126] As an example of the above, the host compound used in the present invention preferably has a partial structure of the following general formula (a) or (b), and may have both partial structures.
[0127] (heteroaromatic ring structure) [ka]
[0128] In the formula, C represents a carbon atom, and R to R 12 represents a hydrogen atom or a substituent. At least one of CR1 to CR4 or CR5R6, or CR7 to CR 12 At least one of the above is substituted with a nitrogen atom, an oxygen atom, or a sulfur atom, and is substituted with a hydrogen atom or a substituent so as to satisfy the valence of each atom. Adjacent CR groups may form a ring. Examples of structures that satisfy this structure include pyrrole, furan, thiophene, imidazole, pyrazole, oxazole, isoxazole, thiazole, pyridine, quinoline, coumarin, benzofuran, indole, acridine, phenoxazine, carbazole, carboline, and dibenzofuran structures.
[0129] (Triarylamine structure) [ka]
[0130] Each of Ar1 to Ar3 independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group, which may have a substituent.
[0131] (electron transport layer) The term "electron transport layer" refers to a layer made of a material having a function of transporting electrons and having a function of transmitting electrons injected from the cathode to the light emitting layer. The total thickness of the electron transport layer is not particularly limited, but is preferably within the range of 2 nm to 5 μm, more preferably within the range of 2 to 500 nm, and even more preferably within the range of 5 to 200 nm.
[0132] A material used in the electron transport layer (hereinafter also referred to as an "electron transport material") may have any one of an electron injecting or transporting property and a hole blocking property.
[0133] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the electron transport material. Among them, the organometallic complex in which the central metal atom or ion M is Ir or Zn is preferable.
[0134] In addition to the above metal complexes, known materials used in the electron transport layer of organic EL devices can be used. The above metal complexes may be used in combination with known materials.
[0135] Examples of known electron transport materials include nitrogen-containing aromatic heterocyclic derivatives (carbazole derivatives, azacarbazole derivatives (one or more of the carbon atoms constituting the carbazole ring are substituted with a nitrogen atom), pyridine derivatives, pyrimidine derivatives, pyrazine derivatives, pyridazine derivatives, triazine derivatives, quinoline derivatives, quinoxaline derivatives, phenanthroline derivatives, azatriphenylene derivatives, oxazole derivatives, thiazole derivatives, oxadiazole derivatives, thiadiazole derivatives, triazole derivatives, benzimidazole derivatives, benzoxazole derivatives, benzothiazole derivatives, etc.), dibenzofuran derivatives, dibenzothiophene derivatives, silole derivatives, aromatic hydrocarbon derivatives (naphthalene derivatives, anthracene derivatives, triphenylene, etc.), and the like.
[0136] In addition, metal complexes having a quinolinol skeleton or a dibenzoquinolinol skeleton in the ligand, such as tris(8-quinolinol)aluminum (Alq3), tris(5,7-dichloro-8-quinolinol)aluminum, tris(5,7-dibromo-8-quinolinol)aluminum, tris(2-methyl-8-quinolinol)aluminum, tris(5-methyl-8-quinolinol)aluminum, bis(8-quinolinol)zinc (Znq), and metal complexes in which the central metal of these metal complexes is replaced with In, Mg, Cu, Ca, Sn, Ga, or Pb can also be used as electron transport materials.
[0137] In addition, metal-free and metal phthalocyanines, and those in which the terminals are substituted with an alkyl group, a sulfonic acid group, etc., can also be preferably used as the electron transport material. Distyrylpyrazine derivatives exemplified as materials for the light-emitting layer can also be used as the electron transport material, and inorganic semiconductors such as n-type Si and n-type SiC can also be used as the electron transport material, as in the hole injection layer and the hole transport layer. Furthermore, it is also possible to use polymer materials in which these materials are introduced into the polymer chain or in which these materials form the polymer main chain.
[0138] The electron transport layer according to the present invention may be doped with a dopant as a guest material to form an electron transport layer with high n-type (electron-rich) properties. Examples of the dopant include n-type dopants such as metal complexes and metal compounds such as metal halides. Specific examples of the electron transport layer having such a configuration include those described in JP-A-4-297076, JP-A-10-270172, JP-A-2000-196140, JP-A-2001-102175, J. Appl. Phys. 95, 5773 (2004), and other documents.
[0139] Specific examples of known electron transport materials include compounds described in the following documents, but the present invention is not limited thereto. U.S. Patent No. 6,528,187, U.S. Patent No. 7,230,107, U.S. Patent Publication No. 2005 / 0025993, U.S. Patent Publication No. 2004 / 0036077, U.S. Patent Publication No. 2009 / 0115316, U.S. Patent Publication No. 2009 / 0101870, U.S. Patent Publication No. 2009 / 0179554, International Publication No. 2003 / 060956, International Publication No. 2008 / 132085, Ap pl.Phys.Lett.75,4(1999), Appl.Phys.Lett.79,449(2001), Appl.Phys.Lett.81,162(2002), Appl.Phys.Lett.8 1,162(2002), Appl.Phys.Lett.79,156(2001), US Patent No. 7964293, US Patent Publication No. 2009 / 030202, International Publication No. 2004 / 080975 No. 2004 / 063159, WO 2005 / 085387, WO 2006 / 067931, WO 2007 / 086552, WO 2008 / 114690, WO 2009 / 069442, WO 2009 / 066779, WO 2009 / 054253, WO 2011 / 086935, WO 2010 / 150593, WO 2010 / 047707, EP2311826, JP2010-251675A, JP2009-209133A, JP2009-124114A, JP2008-277810A, JP2006-156445A, JP2005-340122A, JP2003-45662A, JP2003-31367A, JP2003-282270A, WO2012 / 115034A, and the like.
[0140] Among these, the electron transport material of the present invention is more preferably a pyridine derivative, a pyrimidine derivative, a pyrazine derivative, a triazine derivative, a dibenzofuran derivative, a dibenzothiophene derivative, a carbazole derivative, an azacarbazole derivative, or a benzimidazole derivative. The electron transporting materials may be used alone or in combination of two or more kinds.
[0141] (Hole blocking layer) The term "hole blocking layer" refers to a layer having the function of an electron transport layer in a broad sense. It is preferably made of a material that has the function of transporting electrons but has a small ability to transport holes, and can improve the probability of recombination of electrons and holes by transporting electrons while blocking holes. The above-mentioned configuration of the electron transport layer can be used as a hole blocking layer, if necessary. The hole blocking layer is preferably provided adjacent to the cathode side of the light emitting layer.
[0142] The thickness of the hole blocking layer is preferably within the range of 3 to 100 nm, and more preferably within the range of 5 to 30 nm.
[0143] The material used in the hole blocking layer is preferably the material used in the electron transport layer or the host compound.
[0144] (electron injection layer) The "electron injection layer (also called "cathode buffer layer")" refers to a layer provided between the cathode and the light-emitting layer to reduce the driving voltage and improve the luminance of emitted light. It is described in detail in "Electrode Materials" (pp. 123-166, Chapter 2, Volume 2) of "Organic EL Elements and Their Industrialization Frontiers" (published by NTS Corporation on November 30, 1998).
[0145] The electron injection layer is formed between the cathode and the light emitting layer, or between the cathode and the electron transport layer, as necessary. The electron injection layer is preferably a thin film, and although it depends on the material, the thickness is preferably within a range of 0.1 to 5 nm. Alternatively, the electron injection layer may be a non-uniform film in which the constituent materials are intermittently present.
[0146] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the material used in the electron injection layer. Among them, the organometallic complex in which the central metal atom or ion M is Ir or Zn is preferable.
[0147] In addition to the above metal complexes, known materials used in the electron injection layer of organic EL devices can be used. The above metal complexes may be used in combination with known materials.
[0148] The electron injection layer is also described in detail in JP-A-6-325871, JP-A-9-17574, JP-A-10-74586, etc., and specific examples of materials preferably used for the electron injection layer include metals such as strontium and aluminum, alkali metal compounds such as lithium fluoride, sodium fluoride, potassium fluoride, etc., alkaline earth metal compounds such as magnesium fluoride and calcium fluoride, metal oxides such as aluminum oxide, and metal complexes such as lithium 8-hydroxyquinolate (Liq). The above-mentioned electron transport materials can also be used. These materials may be used alone or in combination.
[0149] (Hole transport layer) The term "hole transport layer" refers to a layer made of a material having a function of transporting holes and having a function of transmitting holes injected from the anode to the light emitting layer. The total thickness of the hole transport layer is not particularly limited, but is preferably within the range of 5 nm to 5 μm, more preferably within the range of 2 to 500 nm, and even more preferably within the range of 5 to 200 nm.
[0150] The material used in the hole transport layer (hereinafter referred to as a hole transport material) may have any one of hole injection or transport properties and electron barrier properties.
[0151] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the hole transport material. Among them, the organometallic complex in which the central metal atom or ion M is Ir or Cu is preferable.
[0152] In addition to the above metal complexes, known materials used in the hole transport layer of an organic EL device can be used. The above metal complexes may be used in combination with known materials.
[0153] Examples of known hole transport materials include porphyrin derivatives, phthalocyanine derivatives, oxazole derivatives, oxadiazole derivatives, triazole derivatives, imidazole derivatives, pyrazoline derivatives, pyrazolone derivatives, phenylenediamine derivatives, hydrazone derivatives, stilbene derivatives, polyarylalkane derivatives, triarylamine derivatives, carbazole derivatives, indolocarbazole derivatives, isoindole derivatives, acene derivatives such as anthracene and naphthalene, fluorene derivatives, fluorenone derivatives, and polyvinylcarbazole, polymeric materials or oligomers having aromatic amines introduced into the main chain or side chain, polysilanes, conductive polymers or oligomers (e.g., PEDOT:PSS, aniline-based copolymers, polyaniline, polythiophene, etc.), and the like.
[0154] Examples of triarylamine derivatives include benzidine type such as α-NPD, starburst type such as MTDATA, and compounds having fluorene or anthracene in the triarylamine linking core part, etc. In addition, hexaazatriphenylene derivatives such as those described in JP-T-2003-519432 and JP-A-2006-135145 can also be used.
[0155] It is also possible to use a highly p-type hole transport material doped with impurities, such as those described in JP-A-4-297076, JP-A-2000-196140, JP-A-2001-102175, J. Appl. Phys., 95, 5773 (2004), and the like.
[0156] Also usable are so-called p-type hole transport materials and inorganic compounds such as p-type-Si and p-type-SiC, as described in JP-A-11-251067 and J. Huang et al. (Applied Physics Letters 80 (2002), p. 139). Furthermore, ortho-metalated organometallic complexes having Ir or Pt as the central metal, as typified by Ir(ppy)3, are also preferably used.
[0157] Among them, triarylamine derivatives, carbazole derivatives, indolocarbazole derivatives, azatriphenylene derivatives, organometallic complexes, polymeric materials or oligomers in which aromatic amines are introduced into the main chain or side chain, etc. are preferably used. Specific examples include the compounds described in the documents listed above and the following documents, but the present invention is not limited to these. The hole transport material may be used alone or in combination of two or more kinds.
[0158] Appl.Phys.Lett.69,2160(1996), J.Lumin.72-74,985(1997), Appl.Phys.Lett.78,673(2001), Appl.Phys.Lett.90,183503 (2007), Appl.Phys.Lett.90,183503(2007), Appl.Phys.Lett.51,913(1987), Synth.Met.87,171(1997), Synth.Met.91,209 (1997), Synth.Met.111,421(2000), SID Symposium Digest, 37, 923 (2006), J. Mater. Chem. 3, 319 (1993), Adv. Mater. 6, 677 (1994), Chem. Mater. 15, 3148 (2003), U.S. Patent Publication No. 2003 / 0162053, U.S. Patent Publication No. 2002 / 0158242, U.S. Patent Publication No. 2006 / 0240279, U.S. Patent Publication No. 2008 / 0220265, U.S. Patent No. 5,061,569, International Publication No. These include WO 2007 / 002683, WO 2009 / 018009, EP650955, U.S. Patent Publication No. 2008 / 0124572, U.S. Patent Publication No. 2007 / 0278938, U.S. Patent Publication No. 2008 / 0106190, U.S. Patent Publication No. 2008 / 0018221, WO 2012 / 115034, JP 2003-519432 A, JP 2006-135145 A, and U.S. Patent Application No. 13 / 585981.
[0159] (electron blocking layer) The term "electron blocking layer" refers, in a broad sense, to a layer having the function of a hole transport layer, and is preferably made of a material that has the function of transporting holes but has little ability to transport electrons, and can improve the probability of recombination of electrons and holes by blocking electrons while transporting holes. If necessary, the above-mentioned hole transport layer may be used as an electron blocking layer according to the present invention. The electron blocking layer is preferably provided adjacent to the anode side of the light emitting layer.
[0160] The thickness of the electron blocking layer is preferably within the range of 3 to 100 nm, and more preferably within the range of 5 to 30 nm.
[0161] In the present invention, the above-mentioned organometallic complex (organometallic complex having the structure represented by the above general formula (1)) can be used as the material used in the electron blocking layer. Among them, organometallic complexes in which the central metal atom or ion M is Ir, Fe, or Cu are preferred.
[0162] In addition to the above metal complexes, known materials used in the electron blocking layer of organic EL devices can be used. Also, the above metal complexes may be used in combination with known materials. As materials used in the electron blocking layer, materials used in the hole transport layer are preferably used, and materials used as the host compounds are also preferably used in the electron blocking layer.
[0163] (Hole injection layer) The "hole injection layer (also called "anode buffer layer")" refers to a layer provided between the anode and the light-emitting layer to reduce the driving voltage and improve the luminance of emitted light. It is described in detail in "Electrode Materials" (pp. 123-166, Chapter 2, Volume 2) of "Organic EL Elements and Their Industrialization Frontiers" (published by NTS Corporation on November 30, 1998). The hole injection layer is, if necessary, formed between the anode and the light emitting layer or between the anode and the hole transport layer as described above.
[0164] In the present invention, the above-mentioned organometallic complex (the organometallic complex having the structure represented by the above general formula (1)) can be used as the material used in the hole injection layer. Among them, the organometallic complex in which the central metal atom or ion M is Ir, Fe or Cu is preferable.
[0165] By using the organometallic complex of the present invention as a material for the hole injection layer, the driving voltage of the organic EL device can be reduced and the efficiency of external extraction can be improved.
[0166] In addition to the above metal complexes, known materials used in the hole injection layer of an organic EL device can be used. The above metal complexes may be used in combination with known materials.
[0167] The hole injection layer is also described in detail in JP-A-9-45479, JP-A-9-260062, JP-A-8-288069, etc., and examples of materials used in known hole injection layers include the above-mentioned hole transport materials.
[0168] Among these, preferred are phthalocyanine derivatives such as copper phthalocyanine, hexaazatriphenylene derivatives as described in JP-T-2003-519432A and JP-A-2006-135145A, metal oxides such as vanadium oxide, amorphous carbon, conductive polymers such as polyaniline (emeraldine) and polythiophene, orthometalated complexes such as tris(2-phenylpyridine)iridium complex, triarylamine derivatives, etc. These materials may be used alone or in combination.
[0169] In the comparative examples in the following examples, copper phthalocyanine and a polythiophene conductive polymer are used as materials for the hole injection layer. When the organometallic complex of the present invention is used as a material for another layer, copper phthalocyanine and a polythiophene conductive polymer are used as suitable materials for the hole injection layer.
[0170] The organic functional layer according to the present invention may contain other compounds. Examples of other compounds include halogen elements such as bromine, iodine, and chlorine, halogenated compounds, alkali metals such as Pd, Ca, and Na, alkaline earth metals, and transition metal compounds, complexes, and salts.
[0171] The content of the other compounds can be determined arbitrarily, but is preferably 1000 ppm or less, more preferably 500 ppm or less, and even more preferably 50 ppm or less, based on the total mass of the layer in which they are contained, although it is not within this range depending on the purpose of improving the transportability of electrons and holes, or for facilitating the energy transfer of excitons.
[0172] (anode) The anode is an electrode that functions to supply holes to the light-emitting layer, and is preferably optically transparent. The thickness of the anode, although depending on the material, is preferably within a range of 10 nm to 1 μm, and more preferably within a range of 10 to 200 nm.
[0173] The material used for the anode is preferably an oxide semiconductor, or a thin film of a metal or alloy, such as metals such as Ag and Au, or alloys mainly composed of metals, CuI, indium-tin oxide (ITO), SnO2, ZnO, or other oxide semiconductors.
[0174] In the case of an anode having optical transparency, it is preferable that the anode is mainly composed of silver, and the purity of the silver is preferably 99% or more. In order to ensure the stability of silver, palladium (Pd), copper (Cu), gold (Au), etc. may be added.
[0175] When the light-transmitting anode is a layer mainly composed of silver, it may be formed of silver alone or an alloy containing silver (Ag). Examples of such alloys include silver-magnesium (Ag-Mg), silver-copper (Ag-Cu), silver-palladium (Ag-Pd), silver-palladium-copper (Ag-Pd-Cu), and silver-indium (Ag-In).
[0176] When the anode according to the present invention is a layer mainly composed of silver, the thickness of the anode is preferably within a range of 2 to 20 nm, more preferably within a range of 4 to 12 nm. By keeping the thickness at 20 nm or less, the absorptive and reflective components of the anode having optical transparency are kept low, and high optical transmittance is maintained.
[0177] In the present invention, the term "layer mainly composed of silver" means that the silver content in the light-transmitting anode is 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 98% by mass or more. The term "light transmittance" means that the light transmittance at a wavelength of 550 nm is 50% or more.
[0178] The layer mainly composed of silver may be configured to be divided into a plurality of layers and laminated as necessary.
[0179] In addition, when the anode is a layer mainly composed of silver and has optical transparency, it is preferable to provide an underlayer thereunder from the viewpoint of making the thickness of the film uniform. The underlayer is not particularly limited, but is preferably a layer containing an organic compound having a nitrogen atom or a sulfur atom.
[0180] The nitrogen atom-containing compound used in the undercoat layer is not particularly limited as long as it is a compound containing a nitrogen atom in the molecule, but is preferably a compound having a heterocycle with a nitrogen atom as a heteroatom. Examples of the heterocycle with a nitrogen atom as a heteroatom include aziridine, azirine, azetidine, azeto, azolidine, azole, azinane, pyridine, azepane, azepine, imidazole, pyrazole, oxazole, thiazole, imidazoline, pyrazine, morpholine, thiazine, indole, isoindole, benzimidazole, purine, quinoline, isoquinoline, quinoxaline, cinnoline, pteridine, acridine, carbazole, benzo-C-cinnoline, porphyrin, chlorine, and choline.
[0181] The nitrogen atom-containing compound used in the underlayer is preferably an aromatic heterocyclic compound having a nitrogen atom with an unshared electron pair that is not involved in aromaticity.
[0182] Specific examples of these nitrogen atom-containing compounds include exemplified compounds No. 1 to No. 134 described in paragraphs (0097) to (0221) of JP-A No. 2015-046364.
[0183] The anode may be formed by forming a thin film of these electrode materials by a method such as vapor deposition or sputtering, and then forming a pattern of a desired shape by a photolithography method. Alternatively, when high pattern accuracy is not required (approximately 100 μm or more), a pattern may be formed through a mask of a desired shape during vapor deposition or sputtering of the electrode material.
[0184] In addition, when a coatable material such as an organic conductive compound is used, a wet film formation method such as a printing method or a coating method can be used. When light is extracted from this anode, it is preferable that the transmittance is greater than 10%, and the sheet resistance of the anode is preferably several hundred Ω / sq. or less.
[0185] (cathode) The cathode is an electrode that functions to supply electrons to the light-emitting layer, and is preferably an electrode that is light-reflective or light-transmissive.
[0186] Materials used for the cathode include metals, alloys, organic or inorganic conductive compounds, or mixtures thereof, such as gold, aluminum, silver, magnesium, lithium, magnesium / copper mixtures, magnesium / silver mixtures, magnesium / aluminum mixtures, magnesium / indium mixtures, indium, lithium / aluminum mixtures, rare earth metals, ITO, ZnO, TiO2, and oxide semiconductors such as SnO2, among which thin film metals or alloys are preferred.
[0187] When the light-transmitting cathode is a layer mainly composed of silver, the same materials as those described above for the anode can be used, and specifically, the cathode can be made of silver alone or an alloy containing silver (Ag). Examples of such alloys include silver-magnesium (Ag-Mg), silver-copper (Ag-Cu), silver-palladium (Ag-Pd), silver-palladium-copper (Ag-Pd-Cu), and silver-indium (Ag-In).
[0188] The cathode can be produced by forming a thin film of these electrode materials by a method such as vapor deposition or sputtering, etc. The sheet resistance of the cathode is preferably several hundred Ω / sq. or less, and the thickness is preferably within the range of 10 nm to 5 μm, and more preferably within the range of 50 to 200 nm.
[0189] From the viewpoint of transmitting the emitted light and improving the luminance of the emitted light, it is preferable that either the anode or the cathode is transparent or semi-transparent. A transparent or semi-transparent cathode can be produced by preparing the above metal with a thickness in the range of 1 to 20 nm and preparing the conductive transparent material described in the description of the anode on top of the metal. In addition, by applying this, an organic EL element in which both the anode and the cathode are transparent can be produced.
[0190] (substrate) The substrate used in the organic EL element of the present invention is not particularly limited and may be transparent or opaque. When light is extracted from the substrate side, the substrate is preferably transparent. Examples of transparent substrates include glass, quartz, and transparent resin films. In addition, from the viewpoint of imparting flexibility to the organic EL element, a resin film having flexibility is more preferable.
[0191] Examples of resin films include polyesters such as polyethylene terephthalate (abbreviation: PET) and polyethylene naphthalate (abbreviation: PEN), polyethylene, polypropylene, cellophane, cellulose esters such as cellulose diacetate, cellulose triacetate (abbreviation: TAC), cellulose acetate butyrate, cellulose acetate propionate (abbreviation: CAP), cellulose acetate phthalate, and cellulose nitrate, and derivatives thereof, polyvinylidene chloride, polyvinyl alcohol, polyethylene vinyl alcohol, syndiotactic polystyrene, polycarbonate (abbreviation: PC), norbornene resin, polymethylpentene, polyether ketone, polyimide, polyether sulfone (abbreviation: PES), polyphenylene sulfide, polysulfones, polyetherimide, polyether ketone imide, polyamide, fluororesin, nylon, polymethyl methacrylate, acrylics and polyarylates, and cycloolefin resins.
[0192] As the cycloolefin resin, commercially available products can be used, and examples thereof include ARTON (registered trademark) manufactured by JSR Corporation and APEL (registered trademark) manufactured by Mitsui Chemicals, Inc.
[0193] Among these resin films, in terms of cost and availability, films such as polyethylene terephthalate (abbreviation: PET), polybutylene terephthalate, polyethylene naphthalate (abbreviation: PEN), and polycarbonate (abbreviation: PC) are preferably used as flexible resin films.
[0194] The resin film may be either an unstretched film or a stretched film.
[0195] The resin film can be produced by a conventionally known general film-forming method. For example, a resin material is melted by an extruder, extruded through a circular die or a T-die, and quenched to produce a substantially amorphous, unoriented, unstretched resin film. In addition, a stretched resin film can be produced by stretching an unstretched resin film in the conveying direction of the resin film (longitudinal axis direction, MD direction) or in a direction perpendicular to the conveying direction of the resin film (horizontal axis direction, TD direction) by a known method such as uniaxial stretching, tenter-type sequential biaxial stretching, tenter-type simultaneous biaxial stretching, or tubular-type simultaneous biaxial stretching. In this case, the stretching ratio can be appropriately selected according to the resin that is the raw material of the resin film, but it is preferably within the range of 2 to 10 times in each of the longitudinal axis and transverse axis directions.
[0196] The thickness of the resin film is preferably within a range of 3 to 200 μm, more preferably within a range of 10 to 100 μm, further preferably within a range of 20 to 80 μm, and particularly preferably within a range of 20 to 50 μm. By reducing the thickness, light can be effectively shielded without increasing the size of the light-shielding portion.
[0197] Examples of glass that can be used as a transparent substrate include soda-lime glass, barium-strontium-containing glass, lead glass, aluminosilicate glass, borosilicate glass, and barium borosilicate glass.
[0198] Examples of opaque substrates include metal plates such as aluminum and stainless steel, film and opaque resin substrates, and ceramic substrates.
[0199] The organic EL element of the present invention preferably has an external extraction quantum efficiency of 1% or more, more preferably 5% or more, at room temperature. The external extraction quantum efficiency is represented by the following formula. External extraction quantum efficiency (%) = number of photons emitted outside the organic EL element / number of electrons flowing into the organic EL element × 100.
[0200] Furthermore, a hue improving filter such as a color filter or a color conversion filter that uses a phosphor to convert the emission color from the organic EL element into multiple colors may be used in combination.
[0201] (Gas barrier layer) In the organic EL device of the present invention, a gas barrier layer may be provided on the substrate described above, if necessary. In particular, when the substrate is a resin film, it is preferable to provide a gas barrier layer.
[0202] The resin film on which the gas barrier layer is formed has a water vapor permeability (25±0.5°C, relative humidity (90±2)% RH) of 0.01 g / (m 2 It is preferable that the oxygen permeability measured by the method according to JIS K 7126-1987 is 10 -3 mL / (m 2 ·24h·atm) or less, water vapor permeability is 10 -5 g / (m 2 It is preferable that the film has a high barrier property of not more than 24 h.
[0203] The material for forming the gas barrier layer may be any material that has a function of suppressing the intrusion of moisture, oxygen, and other substances that cause deterioration of the organic EL element, and inorganic substances such as silicon oxide, silicon dioxide, and silicon nitride are used. Furthermore, from the viewpoint of improving fragility, it is more preferable to have a laminated structure of an inorganic layer and an organic layer made of an organic material. There is no particular restriction on the order of lamination of the inorganic layer and the organic layer, but it is preferable to laminate the two alternately multiple times.
[0204] The method for forming the gas barrier layer is not particularly limited, and for example, a thin film forming method such as a vacuum deposition method, a sputtering method, a reactive sputtering method, a molecular beam epitaxy method, a cluster ion beam method, an ion plating method, a plasma polymerization method, an atmospheric pressure plasma polymerization method, a plasma CVD method, a laser CVD method, a thermal CVD method, a coating method, etc. can be used, but the atmospheric pressure plasma polymerization method as described in JP-A-2004-68143 is particularly preferred. In addition, a method is also preferably used in which a polysilazane-containing liquid is applied by a wet coating method to form a coating film, and then the coating film is dried, and the coating film is irradiated with vacuum ultraviolet light (VUV light) having a wavelength of 200 nm or less to modify the coating film formed, thereby forming a gas barrier layer.
[0205] The thickness of the gas barrier layer is preferably within a range of 1 to 500 nm, and more preferably within a range of 10 to 300 nm. If the thickness of the gas barrier layer is 1 nm or more, the desired gas barrier performance can be exhibited, and if the thickness is 500 nm or less, deterioration of the film quality, such as the occurrence of cracks in a dense silicon oxynitride film, can be prevented.
[0206] (Sealing) The materials used for the organic functional layer and the electrodes have low moisture resistance and are easily oxidized, that is, decomposition and oxidation occur due to water, oxygen, etc. in the environment, so it is preferable to seal the organic functional layer and the electrodes to prevent moisture from entering them. For example, a method of bonding a sealing member to the electrodes and the substrate with an adhesive can be used as the sealing means. The sealing member may be in the form of a concave plate or a flat plate as long as it is arranged to cover the display area of the organic EL element. In addition, there is no particular restriction on the transparency and electrical insulation.
[0207] Specifically, examples of the glass plate include glass plates, polymer plates / films, metal plates / films, etc. Examples of the glass plate include soda lime glass, barium / strontium-containing glass, lead glass, aluminosilicate glass, borosilicate glass, barium borosilicate glass, quartz, etc. Examples of the polymer plate include polycarbonate, acrylic, polyethylene terephthalate, polyether sulfide, polysulfone, etc. Examples of the metal plate include one or more metals or alloys selected from the group consisting of stainless steel, iron, copper, aluminum, magnesium, nickel, zinc, chromium, titanium, molybdenum, silicon, germanium, and tantalum.
[0208] In the present invention, from the viewpoint of thinning the organic EL element, the polymer film or the metal film is preferable. The polymer film has an oxygen permeability of 1×10 or less as measured by a method in accordance with JIS K 7126-1987. -3 mL / m 2 / 24h or less, the water vapor permeability (25±0.5℃, relative humidity (90±2)%) measured by a method conforming to JIS K 7129-1992 is 1×10 -3 g / (m 2 / 24h) or less.
[0209] Methods for processing the sealing member into a concave shape include sandblasting and chemical etching.
[0210] Examples of adhesives include photocurable and heat curable adhesives having reactive vinyl groups, such as acrylic acid oligomers and methacrylic acid oligomers; moisture curable adhesives, such as 2-cyanoacrylic acid esters; heat and chemical curable (two-part mixture) adhesives, such as epoxy-based adhesives; hot melt adhesives, such as polyamide, polyester, and polyolefin; and cationic curable ultraviolet curable epoxy resin adhesives.
[0211] Since the organic EL element may deteriorate due to heat treatment, it is preferable to use an adhesive that can be bonded and cured within a range of room temperature to 80°C. A desiccant may be dispersed in the adhesive. The adhesive may be applied to the sealing portion using a commercially available dispenser or by printing such as screen printing.
[0212] It is also preferable to form a sealing film by covering the electrode and the organic functional layer on the outer side of the electrode facing the substrate with the organic layer sandwiched therebetween and forming an inorganic or organic layer in contact with the substrate. In this case, the material for forming the sealing film may be any material that has a function of suppressing the intrusion of moisture, oxygen, and other substances that cause deterioration of the element, and examples of the material that can be used include silicon oxide, silicon dioxide, silicon nitride, and the like.
[0213] Furthermore, from the viewpoint of improving the fragility of the sealing film, it is preferable to form a laminated structure of these inorganic layers and organic layers. The method for forming the sealing film is not particularly limited, and for example, a vacuum deposition method, a sputtering method, a reactive sputtering method, a molecular beam epitaxy method, a cluster ion beam method, an ion plating method, a plasma polymerization method, an atmospheric pressure plasma polymerization method, a plasma CVD method, a laser CVD method, a thermal CVD method, a coating method, etc. can be used.
[0214] In the gas phase or liquid phase, it is preferable to inject an inert gas such as nitrogen or argon, or an inert liquid such as fluorohydrocarbon or silicone oil into the gap between the sealing member and the display region of the organic EL element. Alternatively, a vacuum may be created, or a hygroscopic compound may be enclosed inside.
[0215] Examples of the hygroscopic compound include metal oxides (e.g., sodium oxide, potassium oxide, calcium oxide, barium oxide, magnesium oxide, aluminum oxide, etc.), sulfates (e.g., sodium sulfate, calcium sulfate, magnesium sulfate, cobalt sulfate, etc.), metal halides (e.g., calcium chloride, magnesium chloride, cesium fluoride, tantalum fluoride, cerium bromide, magnesium bromide, barium iodide, magnesium iodide, etc.), perchlorates (e.g., barium perchlorate, magnesium perchlorate, etc.), and the like. With regard to the sulfates, metal halides, and perchlorates, anhydrous salts are preferably used.
[0216] (protective film, protective plate) A protective film or protective plate may be provided on the outer side of the sealing member or sealing film on the side facing the substrate with the organic functional layer sandwiched therebetween in order to enhance the mechanical strength of the element. In particular, when a sealing film is used, it is preferable to provide such a protective film or protective plate since its mechanical strength is not necessarily high. As materials for the protective film and protective plate, glass plates, polymer plates / films, metal plates / films, etc. can be used as in the sealing member and sealing film, but it is preferable to use polymer films from the viewpoint of light weight and thinness.
[0217] (Light extraction improvement technology) The organic EL element of the present invention generally emits light inside a layer having a refractive index higher than that of air (within the range of a refractive index of 1.6 to 2.1), and only about 15% to 20% of the light generated in the light-emitting layer can be extracted. This is because light incident on an interface (interface between a substrate and air) at an angle θ equal to or greater than the critical angle is totally reflected and cannot be extracted to the outside of the organic EL element, and because light is totally reflected between an electrode or a light-emitting layer and a substrate, and the light is guided through the electrode or the light-emitting layer, resulting in the light escaping in the direction of the side of the organic EL element.
[0218] Examples of methods for improving the light extraction efficiency include a method of forming irregularities on the surface of a substrate to prevent total reflection at the interface between the substrate and the air (e.g., U.S. Pat. No. 4,774,435), a method of improving efficiency by imparting light-collecting properties to the substrate (e.g., JP-A-63-314795), a method of forming a reflective surface on the side surface of an organic EL element (e.g., JP-A-1-220394), a method of introducing a flat layer with an intermediate refractive index between the substrate and the light-emitting layer to form an anti-reflection film (e.g., JP-A-62-172691), a method of introducing a flat layer with a lower refractive index than the substrate between the substrate and the light-emitting layer (e.g., JP-A-2001-202827), and a method of forming a diffraction grating between or within any of the substrate, electrode, and light-emitting layer (JP-A-11-283751).
[0219] In the present invention, it is preferable to use a method of introducing a flat layer having a lower refractive index than the substrate between the substrate and the light-emitting layer, or a method of forming a diffraction grating between or in any of the substrate, electrode, and light-emitting layer.
[0220] By forming a flat layer with a low refractive index (hereinafter also referred to as a "low refractive index layer") between the substrate and the electrode with a thickness longer than the wavelength of light, the lower the refractive index of the low refractive index layer, the higher the efficiency of extracting light to the outside. By combining these means, the present invention can obtain an organic EL element with even higher brightness or excellent durability.
[0221] Examples of materials used to form the low refractive index layer include aerogel, porous silica, magnesium fluoride, fluorine-based polymers, etc. In general, the refractive index of the substrate is within the range of 1.5 to 1.7, so the refractive index of the low refractive index layer is preferably 1.5 or less, and more preferably 1.35 or less.
[0222] In order to prevent evanescent electromagnetic waves from penetrating into the substrate and reducing the effect of the low refractive index layer, the thickness of the low refractive index layer is preferably at least twice the wavelength in the low refractive index layer.
[0223] The method of forming a diffraction grating utilizes the property of a diffraction grating to change the direction of light to a specific direction different from refraction through so-called Bragg diffraction, such as first-order diffraction or second-order diffraction, and diffracts the light generated from the light-emitting layer that cannot escape due to total reflection between layers by introducing a diffraction grating between or within any of the layers of the substrate, electrode, or light-emitting layer, thereby attempting to extract the light to the outside.
[0224] Since the light emitted from the light-emitting layer is generated randomly in all directions, a typical one-dimensional diffraction grating that has a periodic refractive index distribution only in one direction diffracts only light traveling in a specific direction, and the light extraction efficiency does not improve significantly. However, by making the refractive index distribution two-dimensional, light traveling in all directions is diffracted, improving the light extraction efficiency.
[0225] The position where the diffraction grating is formed may be between or within any of the substrate, electrode, and light-emitting layer, but is preferably in the vicinity of the light-emitting layer where light is generated. In this case, the period of the diffraction grating is preferably within a range of about 1 / 2 to 3 times the wavelength of the light in the medium. The arrangement of the diffraction grating is preferably a two-dimensional repeated arrangement such as a square lattice, a triangular lattice, or a honeycomb lattice.
[0226] (Light collecting sheet) The organic EL element of the present invention can be processed to have, for example, a microlens array structure on the light extraction side of the substrate, or can be provided with a light-collecting sheet, thereby enabling light to be collected in a specific direction, for example, in the front direction relative to the light-emitting surface of the organic EL element, and thus enabling the brightness in the specific direction to be increased.
[0227] As an example of a microlens array, a square pyramid with a side of 30 μm and a apex angle of 90 degrees is arranged two-dimensionally on the light extraction side of the substrate. The side is preferably within a range of 10 to 100 μm. By being within the above range, the lens has a light collecting function and can be made sufficiently thin.
[0228] The light-collecting sheet may be, for example, one that is in practical use in LED backlights of liquid crystal display devices, specifically, brightness enhancement film (BEF) manufactured by Sumitomo 3M Ltd. The shape of the prism sheet may be, for example, a base material on which triangle-shaped stripes with an apex angle of 90 degrees and a pitch of 50 μm are formed, or a shape with rounded apex angles, a shape with randomly varying pitch, or other shapes.
[0229] In order to control the light emission angle from the organic EL element, a light diffusion plate / film may be used in combination with the light collecting sheet. For example, a diffusion film (Light Up) manufactured by Kimoto Co., Ltd. may be used.
[0230] <2. Manufacturing method of organic electroluminescence element> The method for producing the organic EL element of the present invention will be described below.
[0231] (Anode formation process) The anode may be made of metals such as Ag and Au or alloys mainly composed of metals, CuI, or indium-tin oxide (ITO), oxide semiconductors such as SnO2 and ZnO, or IDIXO (In2O3-ZnO), which can be used to form amorphous transparent conductive films. A thin film may be formed by deposition or sputtering, and a pattern of the desired shape may be formed by photolithography. If pattern precision is not required (approximately 100 μm or more), a pattern may be formed through a mask of the desired shape during deposition or sputtering of the electrode material. In addition, when a coatable material such as an organic conductive compound is used, a wet film formation method such as a printing method or a coating method may be used.
[0232] (Organic functional layer formation process) A method for forming an organic functional layer (hole injection layer, hole transport layer, light emitting layer, hole blocking layer, electron transport layer, electron injection layer, etc.) according to the present invention will be described. The method for forming the organic functional layer is not particularly limited, and any conventionally known forming method such as a vacuum deposition method or a wet method (also called a wet process) can be used.
[0233] Examples of the wet method include printing methods such as gravure printing, flexographic printing, and screen printing, as well as spin coating, casting, inkjet printing, die coating, blade coating, bar coating, roll coating, dip coating, spray coating, curtain coating, doctor coating, and LB (Langmuir-Blodgett) methods. In view of the ease and high productivity of applying the coating liquid with high accuracy, inkjet printing using an inkjet head is more preferable. Details of the inkjet printing method will be described later. Also, a different film-forming method may be used for each layer.
[0234] The coating liquid used in the wet method may be a solution in which the material for forming the organic functional layer is uniformly dissolved in the liquid medium, or a dispersion in which the material is dispersed as a solid in the liquid medium. Examples of the dispersion method include ultrasonic dispersion, high shear dispersion, and media dispersion.
[0235] The liquid medium is not particularly limited, and examples thereof include halogen-based solvents such as chloroform, carbon tetrachloride, dichloromethane, 1,2-dichloroethane, dichlorobenzene, and dichlorohexanone; ketone-based solvents such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, n-propyl methyl ketone, and cyclohexanone; aromatic solvents such as benzene, toluene, xylene, mesitylene, and cyclohexylbenzene; aliphatic solvents such as cyclohexane, decalin, and dodecane; ester-based solvents such as ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, and diethyl carbonate; ether-based solvents such as tetrahydrofuran and dioxane; amide-based solvents such as dimethylformamide and dimethylacetamide; alcohol-based solvents such as methanol, ethanol, 1-butanol, and ethylene glycol; nitrile-based solvents such as acetonitrile and propionitrile; dimethyl sulfoxide, water, and mixtures thereof.
[0236] From the viewpoint of quickly drying the liquid medium, the boiling point of these liquid media is preferably lower than the temperature of the drying treatment, specifically, preferably within the range of 60 to 200°C, more preferably within the range of 80 to 180°C.
[0237] The coating liquid may contain a surfactant for the purpose of controlling the coating range or suppressing liquid flow associated with the surface tension gradient after coating (for example, liquid flow that causes a phenomenon called coffee ring).
[0238] Examples of the surfactant include anionic or nonionic surfactants from the viewpoints of the effect of moisture contained in the solvent, leveling properties, wettability to the substrate, etc. Specifically, fluorine-containing surfactants and surfactants described in WO 08 / 146681, JP-A 2-41308, etc. can be used.
[0239] The viscosity and thickness of the coating film can be appropriately selected depending on the function required for the organic functional layer and the solubility or dispersibility of the organic material. Specifically, the viscosity of the coating film is preferably within the range of 0.3 to 100 mPa·s, and the thickness is preferably within the range of 1 to 90 μm.
[0240] After forming the coating film by the wet method, it is preferable to have a drying step of removing the liquid medium. The temperature of the drying step is not particularly limited, but is preferably a temperature at which the organic functional layer, the electrode, the substrate, etc. are not damaged. Although it varies depending on the composition of the coating liquid, for example, the temperature of the drying step is preferably within the range of 80 to 300°C, and the time is preferably within the range of 10 seconds to 10 minutes. By being within the above range, rapid drying can be achieved.
[0241] When a deposition method is used to form an organic functional layer, the deposition conditions vary depending on the type of compound used. For example, the boat heating temperature is within the range of 50 to 450°C, and the vacuum degree is 1×10 -6 ~1×10 -2The vapor deposition rate is preferably within the range of 0.01 to 50 nm / sec, and the substrate temperature is preferably within the range of −50 to 300° C. The total thickness of the organic functional layer is preferably within the range of 0.1 nm to 5 μm, and more preferably within the range of 5 to 200 nm.
[0242] It is preferable to form the organic functional layer from the hole injection layer to the cathode in one vacuum step, but it is also possible to take it out midway and apply a different film formation method. In that case, it is preferable to perform the work under a dry inert gas atmosphere.
[0243] (Cathode formation process) After forming the organic functional layer in this manner, a thin film made of the above-mentioned electrode material is formed on the organic functional layer by a method such as vapor deposition or sputtering so as to have a thickness of 1 μm or less, preferably within the range of 10 to 200 nm, to form a cathode. At the same time, a part for connecting to an external power source is formed on the end of the cathode. After forming the cathode, the substrate, anode, organic functional layer, and cathode are sealed with the above-mentioned sealing member.
[0244] <3 Applications of organic EL elements> The organic EL element of the present invention can emit dot light to reproduce patterns or characters, or emit multiple colors to provide a color organic EL device. Examples of light emitting sources include household lighting, car lighting, backlights for clocks and liquid crystal displays, billboard advertisements, traffic lights, light sources for optical storage media, light sources for electrophotographic copiers, light sources for optical communication processors, and light sources for optical sensors. Although not limited thereto, the organic EL element is suitable for electronic devices such as micro LEDs, in which the R (red), G (green), and B (blue) constituting the subpixels of the above-mentioned display are each independent LEDs, since it can realize high pixel resolution.
[0245] [Organic solar cells] Fig. 3 is a schematic diagram showing an example of a solar cell having a single structure (one layer of bulk heterojunction layer) made of a bulk heterojunction type organic photoelectric conversion element. In Fig. 3, a bulk heterojunction type organic photoelectric conversion element 10 has a transparent electrode (anode) 12, a hole transport layer 17, a photoelectric conversion part 14 of the bulk heterojunction layer, an electron transport layer 18, and a counter electrode (cathode) 13 laminated in this order on one side of a substrate 11.
[0246] The substrate 11 is a member that holds the transparent electrode 12, the photoelectric conversion section 14, and the counter electrode 13, which are laminated in this order. Since light to be photoelectrically converted is incident from the substrate 11 side, the substrate 11 is preferably a member that can transmit the light to be photoelectrically converted, that is, a member that is transparent to the wavelength of the light to be photoelectrically converted. For example, glass or a resin film is used as the substrate 11.
[0247] The photoelectric conversion section 14 is a layer that converts light energy into electrical energy, and is configured to have a bulk heterojunction layer in which a p-type semiconductor material and an n-type semiconductor material are uniformly mixed. The p-type semiconductor material functions relatively as an electron donor (donor), and the n-type semiconductor material functions relatively as an electron acceptor (acceptor). Here, the electron donor and electron acceptor are "electron donors and electron acceptors that, when absorbing light, transfer electrons from the electron donor to the electron acceptor to form a hole-electron pair (charge-separated state)", and do not simply donate or accept electrons like an electrode, but donate or accept electrons by a photoreaction.
[0248] In FIG. 3, light incident from the transparent electrode 12 through the substrate 11 is absorbed by the electron acceptor or electron donor in the bulk heterojunction layer of the photoelectric conversion section 14, and electrons move from the electron donor to the electron acceptor, forming pairs of holes and electrons (charge separation state). The generated charges are transported to different electrodes, with the electrons passing between the electron acceptors and the holes passing between the electron donors, due to an internal electric field, for example, a potential difference between the transparent electrode 12 and the counter electrode 13 when the work functions of the transparent electrode 12 and the counter electrode 13 are different, and a photocurrent is detected. For example, when the work function of the transparent electrode 12 is larger than that of the counter electrode 13, the electrons are transported to the transparent electrode 12 and the holes are transported to the counter electrode 13. If the magnitudes of the work functions are reversed, the electrons and holes are transported in the opposite direction. In addition, the transport direction of the electrons and holes can be controlled by applying a potential between the transparent electrode 12 and the counter electrode 13.
[0249] The organometallic complex of the present invention is a compound that easily conducts carriers because it is polarized within the molecule and has an advantage in charge separation, etc. Therefore, it is effective to apply it as a heterojunction type n-type material in solar cells, particularly in organic solar cells.
[0250] The organometallic complex of the present invention can also be used in, for example, heterojunction solar cells formed by stacking an n-type layer and a p-type layer, such as organic EL elements, and bulk heterojunction solar cells in which an n-type compound and a p-type compound coexist in the photoelectric conversion section 14 and the area of the p / n interface is increased by the sea-island structure. EXAMPLES
[0251] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.
[0252] Example 1 [Method of synthesis of metal complex MO-9 by template reaction]
[0253] [ka]
[0254] 2,2'-bipyridyl (23.4 g, 150.0 mmol), 1,5-cyclooctadiene (18.4 mL, 150.0 mmol), bis(1,5-cyclooctadiene)nickel(0) (41.3 g, 150.0 mmol) were added with DMF (62.5 mL) and toluene (62.5 mL) and stirred at 80 °C for 30 min. A solution of compound 2 (3.78 g, 15.0 mmol) in toluene (250 mL) was added dropwise to the mixture over 1 h and stirring was continued at 80 °C for another 16 h. The reaction mixture was cooled to room temperature, 2 M hydrochloric acid (300 mL) was added, and the mixture was stirred vigorously overnight under air. It was extracted with CHCl (400 mL × 3), and the organic layer was washed with saturated brine (200 mL), dried over NaSO, and concentrated in vacuum. The crude product was passed through a silica gel short pass (eluent: CHCl3:MeOH=20:1) and further purified by GPC (YMC T30000, T4000, T2000 columns, solvent: CHCl3) to obtain compound MO-9 as a yellow solid in 57% yield (1.77 g, 1.71 mmol). The obtained MO-9 is in the state of a high-spin complex, and its magnetic properties can also be utilized.
[0255] Example 2 [Method of synthesis of metal complex MO-11: exchange of central metal] As in Example 1, synthesis was carried out in exactly the same manner, except that 10 equivalents of CuCl (14.9 g, 150 mmol) was added to a DMF / toluene solution of 2,2'-bipyridyl, 1,5-cyclooctadiene, and bis(1,5-cyclooctadiene)nickel(0). Mass spectrometry revealed that copper complex MO-11 was produced. By replacing the copper salt used in Example 2 with various metal salts and carrying out a reaction in the presence of these salts, metal species exchange occurred after the CC coupling / cyclization reaction by template reaction, and it was found that it was possible to convert to other metals.
[0256] Example 3 [Preparation of thin film (glowing plastic film) containing MO-9] 10 mg of PMMA (polymethyl methacrylate, Mw: 15,000, Aldrich) and 0.1 mg of MO-9 were added to 1.0 mL of chloroform to prepare a solution with a 1% MO-9 content by mass relative to PMMA. This solution was applied to a 3 cm square quartz substrate, and a thin film containing MO-9 was formed by spin coating. When the obtained thin film was irradiated with 254 nm UV light, a pale light emission originating from the emission of MO-9 in chloroform (353 nm) was observed.
[0257] Example 4 [Organic Electronics Devices] (Preparation of Comparative Organic EL Element 4-1) A glass plate on which a 100 nm ITO (Indium Tin Oxide) film was formed as a first electrode (anode) was ultrasonically cleaned with isopropyl alcohol, dried with dry nitrogen gas and cleaned with UV ozone, and then fixed to a substrate holder in a vacuum deposition device. Next, copper phthalocyanine was evaporated to a thickness of 10 nm to provide a hole injection layer, and α-NPD (4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl) was evaporated on the hole injection layer to provide a hole transport layer with a thickness of 40 nm.
[0258] A host material, CBP (4,4'-bis[9H-carbazol-9-yl]biphenyl), and a light-emitting material, Ir(ppy)3 (tris[2-phenylpyridinato]iridium(III)), were co-evaporated at 94% and 6% by volume, respectively, to form an emission layer with a thickness of 30 nm.
[0259] Then, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) was evaporated to provide an electron transport layer having a thickness of 330 nm, and aluminum was evaporated to provide a second electrode (cathode) having a thickness of 100 nm.
[0260] Next, the following gas barrier film was prepared as a sealing member for the entire organic EL device.
[0261] A polyethylene naphthalate film (manufactured by Teijin Film Solutions Co., Ltd.) was coated on the entire surface thereof with an atmospheric pressure plasma discharge treatment device having the configuration described in JP-A-2004-68143. x The inorganic gas barrier layer is formed to a thickness of 500 nm and has an oxygen permeability of 0.001 mL / (m 2 24h) or less, water vapor permeability 0.001g / (m 2 A flexible gas barrier film with a gas barrier property of less than 24 h was produced.
[0262] A thermosetting liquid adhesive (epoxy resin) was formed as a sealing resin layer on one side of the gas barrier film to a thickness of 25 μm. The gas barrier film with the sealing resin layer was then laminated on the organic EL element prepared above. At this time, the sealing resin layer-forming surface of the gas barrier film was laminated continuously on the sealing surface of the organic EL element so that the ends of the anode and cathode extraction parts were exposed.
[0263] Next, the sample with the gas barrier film attached was placed in a vacuum device and held for 5 minutes under reduced pressure of 0.1 MPa at 90°C. The sample was then returned to an atmospheric pressure environment and further heated at 90°C for 30 minutes to cure the adhesive.
[0264] (Preparation of Organic EL Element 4-2 of the Present Invention) Organic EL element 4-2 was produced in the same manner as in Organic EL element 4-1 produced above, except that the copper phthalocyanine used as the hole injection material was changed to MO-9 synthesized in Example 1. The voltage at the start of light emission of the fabricated organic EL device was measured at a temperature of 23° C. The driving voltage was a current density of 2.5 mA / cm 2 When the voltage value at which the voltage reached 95 was used as a relative evaluation with Organic EL element 4-1 being taken as 100, Organic EL element 4-2 achieved a voltage value of 95, confirming a decrease in the driving voltage and clearly demonstrating the superiority of the material of the present invention.
[0265] Example 5 [Organic Electronics Devices] (Preparation of Comparative Organic EL Element 5-1) A glass substrate on which a 100 nm ITO (Indium Tin Oxide) film was formed as a first electrode (anode) was ultrasonically cleaned with isopropyl alcohol, dried with dry nitrogen gas, and cleaned with UV ozone. Next, a solution of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT / PSS) (Heraeus, CLEVIOS P VP AI 4083) diluted to 70% with pure water was spin-coated at 3000 rpm for 30 seconds, and then dried at 200°C for 1 hour to provide a hole injection layer with a thickness of 30 nm. Next, α-NPD (4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl) was evaporated onto the hole injection layer to provide a hole transport layer with a thickness of 40 nm.
[0266] CBP (4,4'-bis[9H-carbazol-9-yl]biphenyl) as a host material, which is a semiconducting material, and Ir(ppy)3 (tris[2-phenylpyridinato]iridium(III)) as an emissive material were co-evaporated to a volume percentage of 94% and 6%, respectively, to form an emissive layer with a thickness of 30 nm.
[0267] Then, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) was evaporated to provide an electron transport layer having a thickness of 330 nm. Furthermore, aluminum was further evaporated to a thickness of 100 nm to provide a second electrode (cathode).
[0268] Next, the following gas barrier film was prepared as a sealing member for the entire organic EL device. A polyethylene naphthalate film (manufactured by Teijin Film Solutions Co., Ltd.) was coated on the entire surface thereof with an atmospheric pressure plasma discharge treatment device having the configuration described in JP-A-2004-68143. x The inorganic gas barrier layer was formed to a thickness of 500 nm. This resulted in an oxygen permeability of 0.001 mL / (m 2 24h) or less, water vapor permeability 0.001g / (m 2A flexible gas barrier film with a gas barrier property of less than 24 h was produced.
[0269] A thermosetting liquid adhesive (epoxy resin) was formed as a sealing resin layer on one side of the gas barrier film to a thickness of 25 μm. The gas barrier film with the sealing resin layer was then laminated on the organic EL element prepared above. At this time, the sealing resin layer-forming surface of the gas barrier film was laminated continuously on the sealing surface of the organic EL element so that the ends of the anode and cathode extraction parts were exposed.
[0270] Next, the sample with the gas barrier film attached was placed in a vacuum device and held for 5 minutes under reduced pressure of 0.1 MPa at 90°C. The sample was then returned to an atmospheric pressure environment and further heated at 90°C for 30 minutes to cure the adhesive.
[0271] (Preparation of Organic EL Element 5-2 of the Present Invention) Organic EL element 5-2 was produced in the same manner as above, except that a hole injection layer having a thickness of 30 nm was formed by vacuum deposition using MO-11 instead of PEDOT / PSS used in the organic EL element 5-1 produced above. The voltage at the start of light emission of the fabricated organic EL device was measured at a temperature of 23° C. The driving voltage was a current density of 2.5 mA / cm 2 When the voltage value at which the voltage reached 96 was used as a relative evaluation with Organic EL Element 5-1 being taken as 100, Organic EL Element 5-2 achieved a voltage value of 96, confirming a decrease in the driving voltage and clearly demonstrating the superiority of the material of the present invention. [Explanation of symbols]
[0272] 1. Organic EL element 2. Board 3 Anode 4. Hole injection layer 5. Hole transport layer 6. Light-emitting layer 7 Electron transport layer 8 Electron injection layer 9 Cathode F Organic functional layer R recombination L light 10 Bulk heterojunction type organic photoelectric conversion element 11 Substrate 12 Transparent electrode (anode) 13 Counter electrode (cathode) 14 Photoelectric conversion section (bulk heterojunction layer) 17 Hole transport layer 18 Electron transport layer
Claims
1. Having structures represented by the following structural formulae MO-7, MO-8, MO-9, MO-10, MO-11, MO-16, MO-17, MO-18, MO-20, MO-23 and MO-24 1. An organometallic complex comprising: 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】
2. A method for synthesizing an organometallic complex having a structure represented by the following general formula (3), comprising the steps of: The method includes a step of cyclizing the ligand by a coupling reaction in the presence of a metal atom or ion, The metal is Ni or Pd.
1. A method for synthesizing an organometallic complex comprising the steps of: 【Chemistry 4】 (In the formula, R 1 to R 3 each independently represent a hydrogen atom or a substituent; M represents a metal atom or ion other than sodium; n represents a natural number of 4 to 8, and the n R 1 to R 3 are each the same.)
3. The method comprises, after the step of cyclizing the ligand, a step of replacing a central metal atom or ion of the cyclized ligand by a reaction in the presence of a metal salt different from the metal used in the step of cyclizing the ligand. The method for synthesizing an organometallic complex according to claim 2 .
4. Using the method for synthesizing an organometallic complex according to claim 3.
1. A method for synthesizing an organocopper complex comprising the steps of:
5. The organometallic complex according to claim 1 is contained. A film characterized by:
6. The present invention has an organic functional layer containing the organometallic complex according to claim 1. An organic electronics device comprising:
7. The present invention has an organic functional layer containing the organometallic complex according to claim 1. An organic electroluminescence element comprising:
Citation Information
Patent Citations
Organometallic compound, organic light-emitting device including the organometallic compound, and diagnostic composition including the organometallic compound
EP3392257A1
Nitrogen-containing aromatic compound and metal complex
JP2012017314A